Improving Health and Happiness in the Home by Being an Energy Giver Rather Than an Energy Taker - Randall A. Cantrell; Victor W. Harris (EDIS)
One way to improve health and happiness in the home is to work toward becoming an energy giver rather than an energy taker. The first step in doing this is to accept that you have some control regarding the attitude you choose to display during your waking hours. This 3-page fact sheet was written by Randall A. Cantrell and Victor W. Harris, and published by the UF Department of Family, Youth and Community Sciences, October 2012.